ХАЛҚАРО БАҲОЛАШНИ ФИЗИКА ЎҚИТУВЧИЛАРИНИ ТАЙЁРЛАШ ТИЗИМИГА ИНТЕГРАЦИЯЛАШ - Исакова, М.И. (SCIENCE and SOCIETY, 2025)
This article examines the role of international assessments in the system of preparing future physics teachers in Uzbekistan. The study covers the historical development of assessment approaches, the methodological features of testing, and the adaptation of international standards to the national context. Special attention is paid to the implementation of digital technologies, the application of modern psychometric methods, and the intercultural adaptation of test tasks. The results of educational reforms demonstrate that integrating international experience contributes to improving the quality of teacher preparation, enhancing analytical skills, and advancing the system of student knowledge evaluation.